Fatores relacionados à compra de seguros: uma investigação na aquisição de seguro de automóvel - Andrade, Raquel de Cassia (2012)
This present dissertation seeks to identify the behavior of automobile insurance potential consumers, as regards decision-making in scenarios of ambiguity, coupled with the amount of the loss and the self-risk. General objective: Identify the consumer behavior related to the intention to purchase insurance considering ambiguity/risks scenarios, the amount of the loss, the perception of self-risk and insurance legislation knowledge. Through a survey applied directly under a pre-selected target audience, a total of 250 persons received the research profile. Although 196 participants answered the instrument, 95 respondents were regarded as valid (answered all the questions of the research). The survey instrument was split into two blocks: (i) demographic data and ambiguity and (ii) risk scenarios, self-risk, amount of loss and legislation knowledge. The scales used in the present study were categorical or metrics. Before the final application, pre-test was conducted with four respondents, allowing further adjustments. The main results were: (i) in matters relating to the scenario of ambiguity and risk, the intention to purchase proved influential for the scenario of imprecise ambiguity allied with the possibilities of occurrence of theft, which takes into account the probability of recovery of the vehicle (the amount of which depends on the State of the vehicle), since, where both are totally unforeseen circumstances; (ii) regarding the self-risk factors that influence buying intention in imprecise ambiguity environment, the results showed that all factors are significant except to the dangerous drive group; (iii) with respect to demographic variables, the more that stand out are education and income variables; (iv) as the last found, the knowledge of legislation proved to be a positive influence of the intention to purchase a car insurance.